EDITORIAL: KIDNEY TRANSPLANTATION FROM BRAIN DEAD DONORS: WHY AND WHERE DO WE STAND? (Iraqi Journal of Medical Sciences, 2016)
Living organ donation is the most widely practiced type of donation in the Middle East and includes kidney and partial liver. It is predominantly genetically related, however, non-genetically related and commercial living organ donation do exist. Other sources of organ donation include organs obtained from a donor after brain stem death (BD) also called (cadaveric heart beating donors), or donation after cardiac death (DCD) previously known as non – heart beating donation. The objectives of this paper are to explain the rationale of using organs from BD donors, highlight the concept of BD, show legal, religious and ethical related issues and demonstrate the international experience and status of BD organ (kidney) transplantation in Iraq.